Social Capital in Social Forestry Programs in Indonesia: A Bibliometric Analysis (Universitas Terbuka, 2025)
Social forestry research is essential to achieve sustainable management of forest resources, support local livelihoods, and strengthen community institutions. In this context, social capital plays a crucial role in facilitating cooperation and programs success. With the increasing implementation of social forestry programs in Indonesia, understanding existing research patterns is an important first step to identify gaps and future research directions. This study uses bibliometric analysis to assess research trends on social capital in social forestry in Indonesia, using data from the Scopus database. A total of 46 relevant documents were identified and analysed to assess publication patterns, affiliations and knowledge structures. The analysis shows a dynamic publication pattern, with journal articles and conference papers as the main document types. There was a significant increase in the number of publications after 2017, with the highest peak occurring in 2021. Research affiliations are dominated by national institutions such as IPB University, the National Research and Innovation Agency (BRIN), and Gadjah Mada University, with IPB University as the main contributor. Strong international collaboration networks were also identified, particularly with the Centre for International Forestry Research (CIFOR) and universities in Australia. Analysis of keywords, topic trends, and cooccurrence revealed that the research focused on the central pillars of